ANALISIS STRATEGI PEMASARAN COCA-COLA DALAM MENINGKATKAN OMZET PT. COCA-COLA DISTRIBUSI INDONESIA DI KALIMANTAN BARAT - Priyanto, Agus; Sahputra, Rachmat; Tawil, Hamzah (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study analyzes Coca-Cola's marketing strategy in West Kalimantan by considering national economic factors and local market dynamics. Using a qualitative descriptive design with SWOT analysis, this research examines soft drink market conditions, consumer preferences, distribution position of PT Coca-Cola Distribusi Indonesia, and opportunities and challenges in increasing turnover. The results showed that Coca-Cola's marketing strategy in West Kalimantan needs to be adjusted to local consumer preferences and market dynamics. Recommendations include content adjustment based on demographics, local collaboration, and focus on potential economic sectors. This research provides theoretical and practical contributions for Coca-Cola to design more effective marketing strategies in West Kalimantan.